2017
DOI: 10.1007/s00535-016-1304-z
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic vagus nerve regulates Kupffer cell activation via α7 nicotinic acetylcholine receptor in nonalcoholic steatohepatitis

Abstract: Hepatic vagus activity regulates the inflammatory response of Kupffer cells via α7nAChR in NASH development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 50 publications
1
52
0
Order By: Relevance
“…α7nAchR in the vagus nerve plays an important role in the regulation of hepatic inflammation, but this vagal regulation is impaired in individuals with insulin resistance. Although previous studies have reported that acute or chronic α7nAchR impairment exacerbates hepatic inflammation in NAFLD, no previous study has elucidated the effect of α7nAchR impairment on the progression of NASH; that is, the exacerbation of not only inflammation, but also fibrosis. In the present study, using α7KO mice and diet‐induced animal models of NASH, we found that α7nAchR impairment leads to both inflammation and fibrosis related to the exacerbation of NASH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…α7nAchR in the vagus nerve plays an important role in the regulation of hepatic inflammation, but this vagal regulation is impaired in individuals with insulin resistance. Although previous studies have reported that acute or chronic α7nAchR impairment exacerbates hepatic inflammation in NAFLD, no previous study has elucidated the effect of α7nAchR impairment on the progression of NASH; that is, the exacerbation of not only inflammation, but also fibrosis. In the present study, using α7KO mice and diet‐induced animal models of NASH, we found that α7nAchR impairment leads to both inflammation and fibrosis related to the exacerbation of NASH.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we found that α7nAchR deficiency resulted in hepatic pericellular fibrosis in collagen fiber staining, in addition to the increase in the expression of inflammation‐ and fibrosis‐associated genes. Previous studies have reported the association of α7nAchR deficiency with the exacerbation of hepatic inflammation caused by bacterial endotoxins and of inflammation induced by HFD or short‐term MCD loading. However, HFD or short‐term MCD loading is insufficient to induce liver fibrosis, making it difficult to clarify the role of α7nAchR impairment in liver fibrosis, although liver fibrosis, together with hepatic inflammation, is a major manifestation of NASH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…pY-STAT3 signals were slightly induced from CD11-positive macrophages in the liver of ConA-injected animals, suggesting the possible involvement of pY-STAT3 activity in macrophage activation that mediates proin ammatory reactions within the ganglia at the hepatic hilus and the portal space to postganglionic bers that are extended into hepatic vasculature, bile duct, and hepatic parenchyma (McCuskey, 2004;Sutherland, 1964;Skaaring & Bierring, 1976). It was also reported that the activation of α7 nicotinic acetylcholine receptors is involved in VNS-induced anti-in ammation in hepatic cells such as Kupffer cells and hepatic resident macrophages (Wang et al 2003;Hiramoto et al 2008;Nishio et al 2017;Fonseca et al 2019). However, the sequence of events connecting between ACh-releasing vagal efferent bers and AChR-expressing target cells in the liver remains unclear, and thus the characterization of mediators of intercellular cholinergic signaling, if any, should be of great importance to understand VNS-induced anti-in ammation in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, other studies showed that parasympathetic liver nerve activity may inhibit liver inflammation and, accordingly, in the later stages of NAFLD, parasympathetic stimulation may be more effective than sympathetic inhibition (Nishio et al . ). Therefore, more studies are needed to consider neuromodulation as a treatment option.…”
mentioning
confidence: 97%